2019
DOI: 10.1177/2516103219873011
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual and sexual minority adoptive parents’ help-seeking and service satisfaction of pediatricians and mental health providers

Abstract: The aim of our study was to examine the associations between heterosexual and sexual minority adoptive parents’ adoption-related help-seeking and their service satisfaction with pediatricians and mental health providers. We examined associations with (a) satisfaction with pediatricians and (b) understanding of adoption by a mental health provider among adoptive parents who sought advice for adoption-related issues using data drawn from the Modern Adoptive Families study ( N = 1,419). Logistic regressions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In line with this, despite only 41% of adoptive parents have sought adoption-specialized help, these parents perceived the professional support received as more useful than those who requested non-specialized help. This result is in accordance with research showing that adoptive parents greatly value adoption-competent professionals and services [ 15 , 26 , 38 ]. However, our results also demonstrated that the more adoptive parents who sought for adoption-specialized help reported difficulties related to the quality of the parent–child relationship, the less satisfied they were with the help received.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with this, despite only 41% of adoptive parents have sought adoption-specialized help, these parents perceived the professional support received as more useful than those who requested non-specialized help. This result is in accordance with research showing that adoptive parents greatly value adoption-competent professionals and services [ 15 , 26 , 38 ]. However, our results also demonstrated that the more adoptive parents who sought for adoption-specialized help reported difficulties related to the quality of the parent–child relationship, the less satisfied they were with the help received.…”
Section: Discussionsupporting
confidence: 92%
“…However, an interesting and possibly related result was that the more the adoptive parents reported parental difficulties related to children’s problems, the less they were satisfied with the support received. We could argue that adoptive parents are likely to access generalist rather adoption-specialized services to deal with their children’ problems in our country, which are not always perceived by parents as competent in adoption-related issues [ 15 ]. This explanation is likely to be supported by our findings, as adoption-specialized help-seekers in our sample faced greater difficulties related to their own well-being and adoption-specific issues, but similar difficulties related to their children’s behavioral difficulties, when compared to adoptive parents who sought non-specialized professional support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations